Changes in the Eigenpairs Due to the Structure Modification. The Continuous Approach - Skrinar, M.; Umek, A. (Engineering Transactions, 1997)
During the past years, a great deal of time and efforts have been spent in analysing the changes of eigenpairs of the structure due to the reduction of stiffness and especially of cracks as well. These investigations are further used first to identify the crack location and then its magnitude. The whole attention is focussed on cracks and similar types of damage, neglecting the fact that the eigenpairs changes can be also due to other causes, for example variations of the mass. The paper presents the comparison of eigenvector changes due to two types of structure modifications: stiffness and mass variations. The study covers both the discrete approach using finite element method, and also continuous approach. It is evident from both cases that eigenvectors changes different structure modifications exhibit regular patterns and therefore, it is possible to identify not only the location but also to guess the type of the structure modification. Once when the type of the modification is known, it is possible to obtain the magnitude of the modification from the eigenfrequency change.